Concepts of Landscape Planning and Design for the Conservation of Target Species and Target Ecosystems in Biodiversity Management for Sustainable Tourism - Saroinsong, Fabiola B.; Cumentas, Javier M.; Pangemanan, Euis F. S.; Sumakud, Maria Y. M.A. (Yayasan Bina Lentera Insan, 2026)
Conservation-based landscape planning is an increasingly important strategic approach in addressing the challenges of ecosystem degradation and species extinction due to land use change, habitat fragmentation, and climate change. This article aims to analyze how landscape planning can effectively support the conservation of target species and target ecosystems within the framework of sustainable biodiversity management. Through a systematic literature review of 30 articles of reputable international journals (2005–2025), this study identifies the main principles, planning methods, and indicators of success in integrating conservation into landscape spatial planning. The results show that ecosystem-based approaches, connectivity planning, and multi-stakeholder participation are the main foundations in conservation landscape planning. Indicator species and umbrella species are often used as proxies to identify priority areas, while target ecosystems are selected based on their level of uniqueness, threat, and ecological function. The integration of GIS-based spatial data and habitat modeling allows for effective identification of ecological corridors and conservation core areas. Studies also found that long-term success relies heavily on supportive policies, institutional capacity, and local community involvement. This article concludes that holistic and adaptive landscape planning is key to achieving conservation goals while supporting sustainable development. Policy recommendations include strengthening cross-sectoral landscape governance and building technical capacity in evidence-based planning.